Open circuit potential study of stainless steel in environment containing marine sulphate-reducing bacteria - Sahrani, Fathul Karim; Aziz, Madzlan; Ibrahim, Zaharah; Yahya, Adibah (Universiti Kebangsaan Malaysia, 2008)

(untitled)
The corrosion potential of AISI 304 stainless steel coupons influenced by sulphate-reducing bacteria (SRB) has been studied. Pure colony of SRB was isolated from the Malaysia Marine and Heavy Engineering, Pasir Gudang, Johor. Open circuit potential measurements were carried out in variable types of culturing solutions with SRB1, SRB2, combination of SRB1 & SRB2 and without SRBs inoculated. The results showed that the corrosion potential, Eoc increased in the presence of SRBs (in pure and mixed culture) compared to that of control. EDS analysis showed the strong peak of sulphur in coupon containing SRB cultures compared to the control. Environment Scanning Electron Microscope (ESEM) data showed that the high density cell of SRBs were associated with corroding sections of surface steel comparing with non-corroding sections for coupons immersed in VMNI medium containing SRBs.